21st century skills and their influence on the development of oral production in efl students - Villalba Espinoza, Jefferson Moisés (2024)
In the 21st century, education requires a change in the teaching-learning process to be more meaningful, prepared, and demanding people. Integrating 21st-century skills such as critical thinking, communication, collaboration, and creativity is crucial for learning anything and improving language skills. Therefore, it was mandatory to study the “21st-century skills and their influence on the development of oral production in EFL students”. The research was based on the following objectives. The general aim was to determine the 21st-century skills influence on the development of oral production and as specific objectives; analyze the 21st-century skills to Foster oral production, assess the level of oral production skills to identify students’ needs, and design a website that provides plenty of activities in which teacher and students can go through different 21st-century skills align to oral production ability taking into account technology, the most powerful source nowadays. The methodology applied in this research was a mixed research approach. On one hand is quantitative due to the respective numerical results obtained from the pre-test. On the other hand is qualitative because of the information obtained from the observation guide and the interview that were vital to find out students' problems, drawbacks, and needs. After all the instruments were applied, reaserch results showed that most of students of the first bachelorship at Unidad Educativa Santa Mariana de Jesús have difficulties in communicating in the foreign language and most of them and the teacher did not know about the 21st century skills’ attributes. Hence, it was necessary to come up with an idea where students and teacher can interact with a website based on 21st century skills. The research concludes that embedding 21st-century skills and technology within English language education not only improves oral production proficiency but also prepares students for the demands of the modern world, advocating for a holistic and skills-oriented pedagogical framework since critical thinking activities enhance students' ability to articulate and defend their ideas coherently. Collaborative projects fostered teamwork and encouraged the use of English in interactive, real-world scenarios. Creative tasks stimulated linguistic innovation and engagement, while targeted communication exercises improved fluency and confidence.